Sculpting History: A Formal Analysis of Michael Stevenson's *The Fountain of Prosperity* (2006) - Anna Parlane (Index Journal)
Art historian Amy Knight Powell has suggested that a key characteristic of form is its temporal “promiscuity.” Reliably unfaithful to its original moment, form is open to de- and re-contextualisation: as it enters into different settings and new liaisons it is capable of taking on numerous alternative associations. This paper analyses Berlin-based New Zealand artist Michael Stevenson’s *The Fountain of Prosperity (Answers to Some Questions About Bananas)* (2006) in light of Knight Powell’s observation. Focusing on the sculpture’s installation in Stevenson’s 2011 survey exhibition at Sydney’s Museum of Contemporary Art, I uncover a Duchampian methodology underlying Stevenson’s research-based practice. In its use of found material, contemporary research-based art builds on conceptual art, institutional critique and appropriation art practices, and like them is situated within the genealogy of the readymade. However, as with the apparently anti-art gestures of the readymades and conceptual art, the aesthetic motivations and formal innovations of research-based art tend to be neglected. The historical material such artists present is frequently read as a didactic illustration of their archival sources, with the artwork itself reduced to little more than a prompt for a history lesson. By exploiting the promiscuous temporal elasticity of form, works like *The Fountain of Prosperity* in fact demonstrate the sculptural logic that underpins the use of found objects in contemporary art.